AN EXPERIMENTAL STUDY ON THE TEACHING OF SEASONS: MODEL TRANSFORMATION - Cumhur TÜRK; Hüseyin KALKAN; Bekir Yıldırım (International Journal of Eurasia Social Sciences, 2017)
The objective of this study is to examine the effects of teaching the subject of seasons through physical models and virtual reality programs on the expressed models of pre-service teachers. For this purpose, 3 different physical models were developed and 3 different virtual reality programs were used. The study group consists of 100 pre-service science teachers. The study uses quasi-experimental design, which is a true experimental model. The data were obtained by using open-ended question form. The data were collected three times as pre-instruction, post-instruction and long time after instruction (permanence) and the content was analyzed by using content analysis technique. The analyses were conducted in two stages as question by question analysis and integrated analysis which assesses the answers given to all of the questions together. At the end of the analyses, both methods were found to be useful in the teaching of seasons. However, teaching by using physical models was found to be more successful in providing the permanence of learning. In addition, after integrated analyses, it was concluded that teaching with physical models directed students to scientific model, while teaching with virtual reality programs directed students to synthesis model. Based on these results, suggestions were made to extend the use and production of physical models in astronomy education. Finally, points to take into consideration while teaching the subject of seasons were stated.